Regional tensions as a challenge for Latin America integration and South-South cooperation - Ojeda Medina, Tahina (Revista Española de Desarrollo y Cooperación, 2023)
This article proposes to analyze the relationship between development, regionalism and South-South cooperation, as well as to understand the nature of the tensions of these processes in South America.
Keywords: Development; South-South cooperation; Regionalism; Tensions